Iron deficiency and thrombocytosis. Issue 1 (21st November 2016) - Holbro, A.; Volken, T.; Buser, A.; Sigle, J. P.; Halter, J. P.; Passweg, J. R.; Tichelli, A.; Infanti, L.
Abstract : According to many textbooks, iron deficiency (ID) is associated with reactive thrombocytosis. In this study, we aimed to investigate the correlation between serum ferritin levels and platelet counts in a large cohort of healthy blood donors. We included all whole blood and apheresis donors aged 18 years or older with at least one ferritin measurement and one platelet count performed at the same visit between 1996 and 2014. A total of 130 345 blood counts and ferritin measurements obtained from 22 046 healthy donors were analysed. Overall, no correlation between serum ferritin and platelet count was observed ( r = −0.03, ρ = 0.04 for males, and r = 0.01, ρ = −0.02 for females, respectively). Associations remained clinically negligible after adjusting for age, time since previous blood donation, number of donations and restricting the analysis to ferritin deciles. In this large, retrospective single‐centre study, correlations between low ferritin and platelet count in a large and homogeneous cohort of healthy donors were negligible. Further studies in patients with more severe anaemia and patients with inflammation are warranted.